The Dominant Factors of High Scabies Incidence In Indralaya Islamic Boarding School Students South Sumatera, Indonesia - Salvari Gusti Ayu Dwi Putri; Ahmad Ghiffari; Chairil Anwar; Rico Januar Sitorus (Majalah Kedokteran Sriwijaya, 2019)
Scabies is a skin disease caused by infestation towards Sarcoptes scabiei, the condition locally known as "kudis", occurring easily in moist and densely populated vicinities. Kudis was classified into one of the top 10 most prevalent diseases of Ogan Ilir District in 2014. This research was conducted to analyse the relation between air quality and personal hygiene towards the incidences of scabies among students of boarding school Al Ittifaqiah, Indralaya. This research was an epidemiological method using cross-sectional analytic approach, conducted in March 2016. The population were all students of boarding school (1.859 individuals) and the samples selected were 200 respondents with proportional stratified random sampling. The measuring instruments were cardinal scabies physical diagnostic and questionnaire of demographic interviewing, and air quality observation. Obtained results were then analysed with Chi-Square, Logistic Regression Statistical Tests, and correspondence analysis. The result of scabies prevalence was 74.0%. The statistical test has shown that all free variables present relation towards the occurrence of scabies with the p-value < 0.05 except for the variables of temperature and humidity. Logistic Regression testing result yielded the free variable bearing the most dominant influence towards scabies incidence, which was the residential density (OR: 8.117; 95% CI: 3.176-20.745), ventilation (6.712; 1.323-34.066) and age (3.246; 1.555-6.775). The significant relationship of residential density, ventilation, and age towards the occurrence of scabies should be further investigated in order to prepare for elimination programs.